Avoidance of iodine deficiency/excess during pregnancy in Hashimoto’s thyroiditis - van Heek, Lutz; Staudacher, Christiane; Faust, Michael; Chiapponi, Costanza; Mettler, Jasmin; Schmidt, Matthias; Drzezga, Alexander; Dietlein, Markus; Kobe, Carsten (Nuklearmedizin - NuclearMedicine, 2021)
Purpose Hashimoto’s thyroiditis is a common disease that also affects pregnant women. We analyzed to what extent the inflammatory process of Hashimoto’s thyroiditis changes with iodine prophylaxis in pregnant women. The target for immunologic activity was levels of thyroid antibodies (TPO).Methods The data were collected retrospectively from 20 consecutive, pregnant patients who had been diagnosed with Hashimoto’s thyroiditis between 01.12.2012 and 01.12.2014 and had received iodine supplementation with 100 µg (n = 1) or 150 µg (n = 19). At least two measurements of TPO antibody levels taken during pregnancy and one after pregnancy were evaluated for each patient in the study group.Results At the end of pregnancy, the average TPO antibody level for the 20 patients studied was 137 IU/ml (+/–214 IU/ml), the lowest being 16 IU/ml and the highest 1000 IU/ml. Despite iodine prophylaxis, levels of TPO antibodies decreased in 18 patients during pregnancy, falling below the reference value of 35 IU/ml in 5 cases. However, in one patient TPO antibodies increased from 60 IU/ml to 237 IU/ml during pregnancy while in another, levels remained constant at 1000 IU/ml.Conclusion Iodine prophylaxis in pregnant women, taken at a dose of 100 or 150 μg daily was shown to have no negative systemic effects on Hashimoto’s thyroiditis in a group of pregnant women with increased TPO levels, and can therefore be recommended for expectant mothers, including those with this disease.
Keywords: iodine; hashimoto thyroiditis; pregnancy